2017
DOI: 10.3390/buildings7040117
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on the Design of Hospital Outpatient Areas

Abstract: There is a growing interest among healthcare managers and designers in moving towards a 'patient-centred' design of health and care facilities by integrating patient perceptions and expectations of the physical environment where care takes place. Increased interests in physical environments can mostly be attributed to our improved understanding of their role in patients' health outcomes and staff productivity. There is a gap in the literature on users' perspectives on physical settings in the context of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Research has found other variables such as gender, age, visit frequency, wait time, can effect a respondent's feelings about environment satisfaction (Zhao & Mourshed, 2017;Tsai et al, 2007;Bleustein et al, 2014). However, the author contends that although these variables may influence the strength of any positive or negative feelings reported, they do not determine the actual absence or presence of a particular distress or destress factor.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found other variables such as gender, age, visit frequency, wait time, can effect a respondent's feelings about environment satisfaction (Zhao & Mourshed, 2017;Tsai et al, 2007;Bleustein et al, 2014). However, the author contends that although these variables may influence the strength of any positive or negative feelings reported, they do not determine the actual absence or presence of a particular distress or destress factor.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the range and order of factors that patients consider to be the most important to their psychological comfort (Zhao & Mourshed, 2017). This study aims to bridge this research gap through two objectives: to investigate the factors that increase patients' psychological comfort to provide evidence about how patients experience the physical environments of hospital wards and to investigate patients' and medical staff's opinions on the degree of importance and effectiveness of these factors in creating an optimal indoor healing environment in regard to patients' psychological comfort.…”
Section: Optimal Healing Environmentmentioning
confidence: 99%
“…Yisong Zhao and Monjur Mourshed [11] conducted an interesting study about the hospital outpatient area using a survey of patients. This study is in response to the increasing interest in 'patient-centred' design of health and care facilities, especially the hospital waiting areas.…”
Section: Healthcare Environmentsmentioning
confidence: 99%